Setter's performance and attack tempo as determinants of attack efficacy in Olympic-level male volleyball teams - Bergeles, N.; Nikolaidou, E. M. (International Journal of Performance Analysis in Sport, 2011)
Volleyball's sequential nature makes performance in a succeeding action dependent on preceding action's performance. Even though nearly all of second ball contacts originate from the setter, the effect of setter's performance and attack tempo on attack efficacy has received limited attention. This study's purpose was to analyze the probabilistic relationships that might predict attack efficacy relating to setter's performance as a function of attack tempo in Complex I on Olympic-level male teams. Thirty matches (N=30) of sequential set-to-attack actions were evaluated to assess setter's performance and attack efficacy based on a 5-point numerical rating scale (Eom, 1989). Statistics included cross-tabulation procedure to define"pre-match" percentages, repeated measures ANOVA to examine possible differences among attack tempo in attack efficacy and multinomial logistic regression analysis to examine if variations in setter's performance and attack tempo increased or decreased the probabilities of achieving low (defined either as error or attack continuation) as compared to high attack efficacy (defined as gaining a direct point) (P<0.05). Results on odds ratios showed that when setter's preceding performance was excellent so that attackers made 1st or 2nd tempo attacks, the probabilities of gaining a direct point were strongly increased. It is recommended that setters train to provide attackers with quick tempo attacks and attackers train to effectively attack against a double block.